Pemanfaatan Bekatul sebagai Strategi Pemberdayaan Masyarakat untuk Pencegahan Stunting di Desa Silo - Rohmah, Nikmatur; Azza, Awatiful; Nalawati, Ara Nugrahayu; Oktaviana, Kadek Fadila; Palupi, Aliyah Ratnaning; Farishya, Zahrotul Jinani Nur (Ali Institute of Research and Publication, 2025)
Stunting remains a serious child health problem in Indonesia as it has long-term impacts on physical growth, cognitive development, and future productivity. One of the preventive measures that can be implemented is nutrition education based on local resources as a form of community empowerment. This community service activity aimed to improve the knowledge of mothers in Silo Village regarding the benefits of rice bran as an alternative source of nutrition for stunting prevention. The method applied was health education with a participatory approach, involving 24 mothers as participants. Data were analyzed descriptively to present participant characteristics and changes in knowledge. The results showed that the average age of participants was 36.4 years, the majority had a senior high school education, were unemployed, had a monthly income of less than IDR 1,000,000, and an average of two children. About 52.2% of participants had previously attended health education activities. Knowledge of rice bran as an alternative nutritious food increased significantly after the intervention (p=0.002; CI95% 0.225–0.906). These findings indicate that simple nutrition education can effectively improve community understanding of local food potential. In conclusion, the utilization of rice bran can serve as an innovative local-based strategy to support stunting prevention. This activity not only enhanced mothers’ knowledge of local nutrition but also created economic opportunities through the sustainable processing of rice bran–based products. In addition, it encouraged follow-up initiatives in the form of training on rice bran–based food processing, which has the potential to strengthen community self-reliance and empowerment in a sustainable manner.